PENGGUNAAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PAI SISWA - Zainal Muttaqin, Faiz; Anwar, Ahmad (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
This research aims to explore the use of learning media in the context of integrated thematic learning at Al Muhammad Cepu Middle School in the 2023/2024 academic year. This research uses a descriptive qualitative approach. The location of the research was at Al Muhammad Cepu Middle School. The research subjects included the Principal, Deputy Principal, and Class VII Teachers at Al Muhammad Cepu Middle School. The results of the research show that the use of learning media in Integrated Thematic learning in class VII Al Muhammad Cepu Middle School, if designed well, can act as an effective learning media. This media is able to facilitate and improve the quality of learning, increase student learning motivation, support individual learning according to student abilities, and can be used as a tool to convey direct messages. The use of learning media also helps in presenting messages so as not to focus too much on verbalization, as well as overcoming limitations of space, time and sensory power in the learning process. Another supporting factor is the availability of adequate learning media facilities in schools and positive responses from students towards the use of this media. The existence of learning media makes students more interested and motivated to learn, because this media helps clarify the concepts being taught and minimizes boredom in the learning process.